Role of Oxidative Stress and the Identification of Biomarkers Associated With Thyroid Dysfunction in Schizophrenics - Rasool, Mahmood; Malik, Arif; Saleem, Shamaila; Ashraf, Muhammad Abdul Basit; Khan, Altaf Qadir; Waquar, Sulayman; Zahid, Ayesha; Shaheen, Sumaira; Abu-Elmagd, Muhammad; Gauthaman, Kalamegam; Pushparaj, Peter Natesan (Frontiers in Pharmacology, 2021)
Background: Schizophrenics are associated with a deficiency of dietary antioxidants like vitamin B6, B9, and B12 resulting in defective methylation leading to hyperhomocysteinemia. Hyperhomocysteinemia causes mitochondrial DNA damage, oxidative stress, vascular damage, and lipid peroxidation. Oxidative stress and increase in reactive oxygen species result in 8-oxodG production which induces apoptosis of both astrocytes and thyrocytes thus predisposing them to thyroid dysfunction and neurodegeneration. Furthermore, the presence of excessive free radicals increases thyroid thermogenesis causing hyperthyroidism or its excess may cause hypothyroidism by inhibiting iodide uptake. In the present study, we evaluated the various biomarkers associated with thyroid dysfunction in schizophrenics. Materials and Methods: 288 patients suffering from schizophrenia and 100 control subjects were screened for liver function tests (LFTs) such as alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), and total bilirubin (TB). Also, the stress markers, namely malondialdehyde (MDA), homocysteine, cysteine, methionine, the thyroid profile including triiodothyronine (T3), thyroxine (T4), thyroid-stimulating hormone (TSH), thyroxine peroxide antibody (TPO-Ab); TSH receptor-Ab (TSHr-Ab) and the dietary antioxidants were evaluated using several biochemical analysis. Results: The LFTs showed elevated levels of ALT (45.57±4.87 Vs 26.41±3.76 U/L), AST (40.55±1.34 Vs 21.92±3.65 U/L), ALP (121.54±4.87 Vs 83.76±5.87 U/L), and total bilirubin (2.63±0.987 Vs 1.10±0.056 mg/dl), in schizophrenics than controls. Increased levels of MDA (3.71±0.967 Vs 1.68±0.099) and homocysteine (17.56±2.612 Vs 6.96±1.987 μmol/L were observed in schizophrenics compared to the controls, indicating increased stress. Levels of cysteine and methionine were decreased in schizophrenics than the controls (1.08±0.089 Vs 4.87±.924 μmol/L and 17.87±1.23 Vs 99.20±5.36 μmol/L). The levels of TPO-Ab (IU/ml), Tg-Ab (pmol/L), and TSHr-Ab (IU/L) were observed to be higher in the patients’ group as compared to control subjects (9.84 ± 2.56 Vs 5.81 ± 1.98, 55.50 ± 2.98 Vs 32.95 ± 2.87 and 2.95 ± 0.0045 Vs 1.44 ± 0.0023 respectively). Conclusions: The schizophrenics, demonstrated altered liver function, increased stress markers, and decreased dietary antioxidants. Reduced primary and secondary antioxidant levels, may result in hyperhomocysteinemia and cause further DNA and mitochondrial damage. Therefore, homocysteine and/or prolactin levels may serve as candidate prognostic markers for schizophrenia.